71) Сделаем замену
x² + 3x - 20 = m
Тогда x² + 3x + 2 = m + 22
m(m + 22) = 240
m² + 22m - 240 = 0
d= 22² - 4 * (- 240) = 484 + 960 = 1 444 = 38²
![m_{1}= \frac{-22+38}{2}=8\\\\m_{2}= \frac{-22-38}{2}=-30 m_{1}= \frac{-22+38}{2}=8\\\\m_{2}= \frac{-22-38}{2}=-30](https://tex.z-dn.net/?f=m_%7B1%7D%3D%20%5Cfrac%7B-22%2B38%7D%7B2%7D%3D8%5C%5C%5C%5Cm_%7B2%7D%3D%20%5Cfrac%7B-22-38%7D%7B2%7D%3D-30)
x² + 3x - 20 = 8
x² + 3x - 28 = 0
D = 3² - 4 * (- 28) = 9 + 112 = 121 = 11²
![x_{1}= \frac{-3+11}{2}=4\\\\x_{2}= \frac{-3-11}{2}=-7 x_{1}= \frac{-3+11}{2}=4\\\\x_{2}= \frac{-3-11}{2}=-7](https://tex.z-dn.net/?f=x_%7B1%7D%3D%20%5Cfrac%7B-3%2B11%7D%7B2%7D%3D4%5C%5C%5C%5Cx_%7B2%7D%3D%20%5Cfrac%7B-3-11%7D%7B2%7D%3D-7)
x² + 3x - 20 = - 30
x² + 3x + 10 = 0
D = 3² - 4 * 10 = 9 - 40 = - 31 < 0 - корней нет
Ответ : - 7 ; 4
2) x² - x = p тогда
( p + 8)(p - 6) = 120
p² - 6p + 8p - 48 = 120
p² + 2p - 168 = 0
D = 2² - 4 * ( - 168) = 4 + 672 = 676 = 26²
![p_{1}= \frac{-2+26}{2}=12\\\\p_{2}= \frac{-2-26}{2}=-14 p_{1}= \frac{-2+26}{2}=12\\\\p_{2}= \frac{-2-26}{2}=-14](https://tex.z-dn.net/?f=p_%7B1%7D%3D%20%5Cfrac%7B-2%2B26%7D%7B2%7D%3D12%5C%5C%5C%5Cp_%7B2%7D%3D%20%5Cfrac%7B-2-26%7D%7B2%7D%3D-14)
x² - x = 12
x² - x - 12 = 0
D = (-1)² - 4 * (- 12) = 1 + 48 = 49 = 7²
![x_{1} =\frac{1+7}{2}=4\\\\x_{2}= \frac{1-7}{2}=-3 x_{1} =\frac{1+7}{2}=4\\\\x_{2}= \frac{1-7}{2}=-3](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%5Cfrac%7B1%2B7%7D%7B2%7D%3D4%5C%5C%5C%5Cx_%7B2%7D%3D%20%5Cfrac%7B1-7%7D%7B2%7D%3D-3)
x² - x = - 14
x² - x + 14 = 0
D = (- 1)² - 4 * 14 = 1 - 56 = - 55 < 0 - корней нет
Ответ : - 3 ; 4